Effect of the COVID-19 Pandemic on the Educational Indicators in the Dentistry Career of the University of Costa Rica - Gutiérrez-Marín, Natalia (2024)
This study aimed to determine the effect of the COVID-19 pandemic on the educational indicators of students who enrolled in the dentistry program at the University of Costa Rica between 2015 and 2021. Records of 522 students were analyzed, considering variables such as gender, age at entry, nationality, marital status, children, place and type of high school attended, and course performance. Information was extracted from the Student Applications System, physical records, and the Civil Registry of Costa Rica. Descriptive and bivariate analyses were performed to identify patterns and correlations between variables, and approval rates before and during the pandemic were evaluated. Seventy percent of the students were women, predominantly Costa Rican, aged between 19 and 23, from public high schools, and originating from the Greater Metropolitan Area. Terminal efficiency was zero due to the closure of clinical courses in 2020, which prevented the 2015 to 2017 cohorts from graduating within 12 semesters. The dropout rate was highest in the first and second semesters, with a progressive decrease in subsequent semesters. Most cohorts experienced delays, particularly in semesters 7-8 and 9-10. First-attempt approval rates increased in some service courses with virtualization during the pandemic, such as Intensive General Chemistry and Elementary Mathematics, but no difference was observed in the courses specific to the School of Dentistry. The COVID-19 pandemic had varying impacts on educational indicators, with virtualization improving performance in some theoretical courses while posing challenges in those with practical and clinical components.